2000
DOI: 10.1007/s004210000253
|View full text |Cite
|
Sign up to set email alerts
|

Total energy expenditure of elite synchronized swimmers measured by the doubly labeled water method

Abstract: To determine the daily energy requirement of elite synchronized swimmers during moderate-intensity training, the average daily energy expenditure measured by the doubly labeled water method, was calculated for nine female Japanese national team synchronized swimmers [four senior; mean (SD) 22.5 (1.0) years old, 52.2 (3.6) kg, and five junior; 17.6 (1.1) years old, 52.8 (2.3) kg]. Their total energy expenditure (TEE) was 11.5 (2.8) MJ x day(-1) [2738 (672) kcal day(-1)]. When compared with estimated energy requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
2
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 17 publications
1
61
2
1
Order By: Relevance
“…While a few DLW studies have been con ducted in elite athletes (12,13) and firefighters (14), no study, to the best of our knowledge, has been published on the accuracy of EI among ordinary Japanese people. Furthermore, because the ways people interpret and respond to dietary assessment methods may be different between Western countries and Japan mainly because of large differences in dietary habits, the accuracy of dietary assessment methods may also be different, mak ing it difficult to extrapolate the findings in Western countries to Japanese people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a few DLW studies have been con ducted in elite athletes (12,13) and firefighters (14), no study, to the best of our knowledge, has been published on the accuracy of EI among ordinary Japanese people. Furthermore, because the ways people interpret and respond to dietary assessment methods may be different between Western countries and Japan mainly because of large differences in dietary habits, the accuracy of dietary assessment methods may also be different, mak ing it difficult to extrapolate the findings in Western countries to Japanese people.…”
Section: Discussionmentioning
confidence: 99%
“…The basis of the study was a measurement of TEE by ACC (study days 6-32) with a collection of data on dietary intake using 7dWR (days 5-11) and DHQ (day 8) and on behavioral and psycho logical characteristics using questionnaires (days [8][9][10][11][12] and anthropometric measurements (days 5, 12, and 33). The subjects were strongly encouraged not to change their dietary habits or lifestyle during the study.…”
Section: Methodsmentioning
confidence: 99%
“…The technique is similar to that used by Konrad et al [17]; however, combustion of FAMEs to H 2 or H 2 H before injection into the isotope-ratio mass spectrometer (IRMS) was not required. FAME samples were injected into a GC and effluent was pyrolysed in a furnace at 1,450°C to form H 2 [22].…”
Section: Estimation Of Fatty Acid Synthesis Bymentioning
confidence: 99%
“…Hill et al 19) reported that the average (± SD) PAL was 2.85 (± 0.9) in female light-weight rowers. In addition, Ebine et al 6) found that the mean (± SD) PAL was 2.18 (± 0.43) in female synchronized swimmers. Thus, even among individuals participating in the same sporting category, the same sport, or the same team, PAL varied greatly.…”
Section: Discussionmentioning
confidence: 98%
“…The JISS PALs in the training season were determined based on only seven previous studies using the doubly labeled water (DLW) method in athletes from seven different sports [2][3][4][5][6][7][8] . The JISS PALs for "explosive sports" and "ball sports" were based on the fact that nearly 75% of Japanese athletes showed PAL values of 2.2 or less, and the mean PAL reported in the previous studies was 2.03.…”
Section: Introductionmentioning
confidence: 99%